2015
DOI: 10.1186/s12910-015-0065-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of medical litigation filed against obstetrics and gynecology, internal medicine, and surgery departments

Abstract: BackgroundThe aim of this study was to review the typical factors related to physician’s liability in obstetrics and gynecology departments, as compared to those in internal medicine and surgery, regarding a breach of the duty to explain.MethodsThis study involved analyzing 366 medical litigation case reports from 1990 through 2008 where the duty to explain was disputed. We examined relationships between patients, physicians, variables related to physician’s explanations, and physician’s breach of the duty to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
1
13
1
1
Order By: Relevance
“…8,[14][15][16][17][18][19][20][21][22][23][24][25] Failings in assessment and diagnosis typically included errors of judgement. 16,[24][25][26][27][28] Yamada et al 25 observed 780 algorithmdriven tasks and found that 194 of them (error rate of 23%) were completed incorrectly. They noted that 72% of all errors were errors of commission and 28% were errors of omission.…”
Section: Discussionmentioning
confidence: 99%
“…8,[14][15][16][17][18][19][20][21][22][23][24][25] Failings in assessment and diagnosis typically included errors of judgement. 16,[24][25][26][27][28] Yamada et al 25 observed 780 algorithmdriven tasks and found that 194 of them (error rate of 23%) were completed incorrectly. They noted that 72% of all errors were errors of commission and 28% were errors of omission.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan both maternal and perinatal mortality rates remain low, and healthcare safety in obstetrics and gynecology department is considered to be excellent from a global perspective, and despite such good care, the percentages of medical negligence cases filed against obstetricians are increasing [7]. Issues related to pregnancy and child birth attracts more law suits as pregnancy is believed to be a physiological process, and any deviation from normal is considered to be abnormal [8].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding obstetrics and gynaecology in developed countries, despite low maternal and infant mortality rates and the fact that safety in specialty departments is considered excellent, complaints against gynaecologists continue to rise, especially when compared with other specialties. 19 The most common grounds leading to these claims, however, are the same throughout the world: neonatal encephalopathy, errors in prenatal diagnosis, shoulder dystocia, and errors in the screening of certain diseases. 16 Another reason people focus on complaints against gynaecologists is their influence on changing attitudes in specific aspects of childbirth, which has led to an unjustified increase in the rate of Caesarean sections and low rates of assisted delivery.…”
Section: Discussionmentioning
confidence: 99%